The Effect of Company Size, Profitability, and Leverage on Profit Management (Empirical Study of Manufacturing Companies in the Food and Beverage Subsector Listed on the Indonesia Stock Exchange 2020-2024) - Wardatul Mila; Rieska Maharani; Dedy Surahman (P3I UMSurabaya, 2025)
This research aimed to examine the influence of company size, profitability, and leverage on profit management in manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. The research used a quantitative approach with a descriptive type of research. The research population was 95 companies, with a sample of 39 companies selected using the purposive sampling method. The dependent variable was profit management which was measured using the De Angelo (Non-Discretionary Accruals/NDA) model. Meanwhile, independent variables included company size (SIZE) measured using the natural logarithm of total assets, profitability using Return on Assets (ROA), and leverage using Debt to Asset Ratio (DAR). The data analysis technique used multiple linear regression and classical assumption tests. The results showed that company size, profitability, and leverage partially had no significant effect on profit management. It showed that these three variables were not the dominant factors influencing profit management practices in the food and beverage subsector during the research period.